2021
DOI: 10.1002/jsfa.11349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defect action level of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) fragments on quality of wheat flour

Abstract: BACKGROUND Tribolium castaneum (Herbst) is one of the most important secondary storage pests of all types of flour and flour‐based products. The present study focuses on the fragment producing behaviour of T. castaneum in wheat flour during storage and its effect on the quality parameters and defect action level (DAL) of fragments. The US Food and Drug Administration has set a DAL of 75 insect fragments in 50 g of flour. Box–Behnken design was used to optimize the storage conditions (storage period in days and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Te use of the 2 4 factorial design revealed that the only variable, which signifcantly infuenced the digestion of the wheat four sample, was the temperature, as refected in the MR data; no statistically signifcant efects (at the 95% confdence level) were observed for the interactions between the variables.…”
Section: Optimization Of the Microwave-assisted Digestionmentioning
confidence: 75%
See 1 more Smart Citation
“…Te use of the 2 4 factorial design revealed that the only variable, which signifcantly infuenced the digestion of the wheat four sample, was the temperature, as refected in the MR data; no statistically signifcant efects (at the 95% confdence level) were observed for the interactions between the variables.…”
Section: Optimization Of the Microwave-assisted Digestionmentioning
confidence: 75%
“…Tus, wheat cultivation is important in many cultures, both economically and nutritionally [4,5]. In Saudi Arabia, the popularity of wheat as a food product stems from its versatility, as it is used in pizza dough, diferent kinds of bread, including hamburger buns, and traditional bakery products.…”
Section: Introductionmentioning
confidence: 99%
“…The selective pressure of the environment favoured this structural adaptation, likely due to the presence of the peritrophic matrix throughout the intestinal lumen, which prevents pathogens from passing through the intestinal epithelium into the hemocoel and causing infection (Caccia et al, 2019; Terra, 2001). However, this morphological and functional organisation has the potential to compromise the quality of stored foods following infestations with T. castaneum and contribute to their microbiological contamination (Negi et al, 2022), as bacteria are excreted through faeces. This is a health and economic concern, as demonstrated by recent studies, showing that the red flour beetle could act as a vector of important pathogens in poultry and livestock feed and contribute to the spread of antibiotic‐resistant species, such as enterococci (Channaiah et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of T. castaneum can also result in the development of toxins such as benzoquinones and aflatoxins [ 13 , 20 ]. In addition, parts of dead insects can affect the quality of the wheat flour by increasing its water content, microbial fauna, and uric acid content, as well as changing the color of the flour [ 23 ]. These changes in physical and biochemical properties induced by the high level of humidity and the presence of insects explain the degradation of the organoleptic qualities of the wheat flour stored in PP bags for six months and its lower sensory scores among Afghan women.…”
Section: Discussionmentioning
confidence: 99%